SOCIAL CONFLICTS IN CHARITIES: REASONS, CONSEQUENCE SAND WAYS OF SOLVING THEM - O. Andrienko (Вестник университета, 2017)
The article deals with the origin of social conflicts of international charities by addressing to a science of conflictology, it also emphasizes the difference between egoism and altruism related motivation of the parties involved into a charity process; it argues about the charity act in terms of semiotics and shows the ways of solving these problems in accordance to cultural, social and psychological features which reflect the modern society.